2020
DOI: 10.1111/insr.12393
|View full text |Cite
|
Sign up to set email alerts
|

An Extensive Comparison of Some Well‐Established Value at Risk Methods

Abstract: Summary In the last two decades, several methods for estimating Value at Risk have been proposed in the literature. Four of the most successful approaches are conditional autoregressive Value at Risk, extreme value theory, filtered historical simulation and time‐varying higher order conditional moments. In this paper, we compare their performances under both an empirical investigation using 80 assets and a large Monte Carlo simulation. From our analysis, we conclude that most of the methods seem not to imply h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(97 reference statements)
0
5
0
Order By: Relevance
“…Although there are several methods to forecast the VaR and ES in the literature (see Bayer & Dimitriadis, 2020; Calmon et al, 2020, Nieto & Ruiz, 2016; Righi & Ceretta, 2015, for interesting reviews), only a few procedures have shown good performance in cryptocurrency markets. Those procedures are briefly described next.…”
Section: Var and Es Forecastingmentioning
confidence: 99%
“…Although there are several methods to forecast the VaR and ES in the literature (see Bayer & Dimitriadis, 2020; Calmon et al, 2020, Nieto & Ruiz, 2016; Righi & Ceretta, 2015, for interesting reviews), only a few procedures have shown good performance in cryptocurrency markets. Those procedures are briefly described next.…”
Section: Var and Es Forecastingmentioning
confidence: 99%
“…When applied to the S&P 500 in a period of turmoil, the proposed approach gave VaR limits that were only exceeded four times; accurate estimates of the shortfall incurred on these days were also provided. When applied to the S&P 500 in a less turbulent period, the proposed approach showed an improved performance compared to GARCH-EVT, which Calmon et al (2020) identified as the leading approach for estimating VaR. The proposed approach is the only one that consistently quantified the market risk in both periods.…”
Section: Discussionmentioning
confidence: 94%
“…The S&P 500 exhibits conditional heteroscedasticity, which needs to be filtered via generalized autoregressive conditional heteroscedastic (GARCH) modelling before one can focus on the distribution of the innovations. This type of modelling was used by Calmon et al (2020) in an extensive comparison of existing VaR forecasting methods. Their empirical analysis was based on S&P 500 returns from May 30, 2013 to May 1, 2017, which was a period of relatively standard market behaviour.…”
Section: Application To Financial Market Riskmentioning
confidence: 99%
See 2 more Smart Citations